In vivo Multiphoton Microscopy Technique to Reveal the Physiology of the Mouse Uterus. (24th December 2012) - Zenclussen, Ana C.; Olivieri, David N.; Dustin, Michael L.; Tadokoro, Carlos E.
<x xml:space="preserve">Abstract</x> Problem Pregnancy is a challenge to the maternal immune system as it allows the growing of a semiallogeneic fetus within the uterus. Such tolerance suggests a set of complex cellular distributions and interactions inside the organ. Until now, direct observation of such processes was absent because proper intravital imaging techniques were not available. Method We developed a new two‐photon microscope stage together with a set of surgical procedures to provide direct observation of immune cell within the mouse uterus. Results Using our technique, we observed an accumulation of dendritic cells (DCs) in the uterus during the estrus phase of the estrus cycle. Some of the observed DC clusters were located near the lumen of the uterus or small blood vessels, each situated on the antimesometrium side. Conclusion While two‐photon microscopy has become a widely used technology for intravital imaging, new advances in the development of staging and experimental protocols can still push the limits of this technique for exploring new biology. As proof of this, we demonstrated that with specially designed staging and surgical protocols, we observed the formation of DC clusters in the uterus; structures that may play a role in the complex immunology of the uterus–fetal interface.